2016
DOI: 10.1093/humrep/dew158
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation in female oncology patients: the influence of the type of cancer on ovarian stimulation response

Abstract: The authors have not received any funding to support this study. There are no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 46 publications
3
46
1
2
Order By: Relevance
“…It was previously registered that the number of oocytes retrieved in breast cancer patients with BRCA1 mutations is significantly lower compared to BRCA negative and untested patients [ 34 ]. On the other hand, it was recently described that women with gynecological cancer have less number of retrieved mature oocytes compared with haematological and breast cancer patients [ 35 ]. Interestingly, it was also recently reported that both healthy and cancer-affected BRCA mutation women have normal response to COS in IVF cycles [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously registered that the number of oocytes retrieved in breast cancer patients with BRCA1 mutations is significantly lower compared to BRCA negative and untested patients [ 34 ]. On the other hand, it was recently described that women with gynecological cancer have less number of retrieved mature oocytes compared with haematological and breast cancer patients [ 35 ]. Interestingly, it was also recently reported that both healthy and cancer-affected BRCA mutation women have normal response to COS in IVF cycles [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alvarez et al assessed the influence of different type of cancer on the ovarian response to COS analysing the results of 306 patients. Patients with gynaecological cancer had fewer oocytes retrieved comparing to patients with haematological or breast cancer (Alvarez & Ramanathan, 2016)…”
mentioning
confidence: 94%
“…This cytotoxicity is reversible in organs with a high cell division rate, such as bone marrow, gastro-intestinal tract or thymus, for example. The ovaries, on the other hand, are damaged by chemotherapy to varying degrees because of their limited number of cells with no potential for replication or regeneration of the follicles 8 , 9 . This can result in permanent infertility of the affected women, see Tables 1 and 2 .…”
Section: Introductionmentioning
confidence: 99%
“…B. Knochenmark, GI-Trakt oder Thymus, reversibel. Die Ovarien hingegen werden aufgrund ihrer begrenzten Zellzahl mit fehlender Replikation und Regeneration der Follikel durch die Chemotherapie in unterschiedlichem Ausmaß geschädigt 8 , 9 . Dies kann zu einer permanenten Infertilität der betroffenen Frauen führen, siehe Tab.…”
Section: Introductionunclassified